Microdistribution of lead in human teeth using microbeam synchrotron radiation X‐ray fluorescence (μ‐SRXRF). (28th October 2016) - Wang, Yufei; Specht, Aaron; Liu, Yingzi; Finney, Lydia; Maxey, Evan; Vogt, Stefan; Zheng, Wei; Weisskopf, Marc; Nie, Linda H
Abstract : Lead (Pb) exposure is known to be associated with adverse effects on human health, especially during the prenatal period and early childhood. The Pb content in teeth has been suggested as a useful biomarker for the evaluation of cumulative Pb exposure. This study was designed to employ the microbeam synchrotron radiation X‐ray fluorescence technique to determine the microdistribution of Pb within the tooth to evaluate the reliability of the technique and the effectiveness of tooth Pb as a biomarker of Pb exposure. The results showed that in the incisor sample, Pb primarily deposited in secondary dentine region close to the pulp and secondarily at enamel exterior. In addition, Pb colocalised with Zn, indicating a positive correlation between Pb and Zn. By contrast, in the two molar samples, Pb accumulated principally in the pulp, and secondarily in the enamel. At the same time, Pb in these two molar samples colocalised with Ca instead of Zn as was observed in the incisor sample. Several batches of line scans further confirmed the conclusions. The feasibility of using microbeam synchrotron radiation X‐ray fluorescence to determine the microdistribution of Pb in teeth and of using the tooth Pb, especially in dentine, as a biomarker was discussed. Copyright © 2016 John Wiley & Sons, Ltd.